Light Limitation and Depth-Variable Sedimentation Drives Vertical Reef Compression on Turbid Coral Reefs - Morgan, Kyle M.; Moynihan, Molly A.; Sanwlani, Nivedita; Switzer, Adam D. (Frontiers in Marine Science, 2020)
Turbid coral reefs experience high suspended sediment loads and low-light conditions that vertically compress the maximum depth of reef growth. Although vertical reef compression is hypothesized to further decrease available coral habitat as environmental conditions on reefs change, its causative processes have not been fully quantified. Here, we present a high-resolution time series of environmental parameters known to influence coral depth distribution (light, turbidity, sedimentation, currents) within reef crest (2–3 m) and reef slope (7 m) habitats on two turbid reefs in Singapore. Light levels on reef crests were low [mean daily light integral (DLI): 13.9 ± 5.6 and 6.4 ± 3.0 mol photons m–2 day–1 at Kusu and Hantu, respectively], and light differences between reefs were driven by a 2-fold increase in turbidity at Hantu (typically 10–50 mg l–1), despite its similar distance offshore. Light attenuation was rapid (KdPAR: 0.49–0.57 m–1) resulting in a shallow euphotic depth of <11 m, and daily fluctuations of up to 8 m. Remote sensing indicates a regional west-to-east gradient in light availability and turbidity across southern Singapore attributed to spatial variability in suspended sediment, chlorophyll-a and colored dissolved organic matter. Net sediment accumulation rates were ∼5% of gross rates on reefs (9.8–22.9 mg cm–2 day–1) due to the resuspension of sediment by tidal currents, which contribute to the ecological stability of reef crest coral communities. Lower current velocities on the reef slope deposit ∼4 kg m2 more silt annually, and result in high soft-sediment benthic cover. Our findings confirm that vertical reef compression is driven from the bottom-up, as the photic zone contracts and fine silt accumulates at depth, reducing available habitat for coral growth. Assuming no further declines in water quality, future sea level rise could decrease the depth distribution of these turbid reefs by a further 8–12%. This highlights the vulnerability of deeper coral communities on turbid reefs to the combined effects of both local anthropogenic inputs and climate-related impacts.